Microfinance Institutions as Catalysts for Sustainable Entrepreneurship: Examining the Role of Social Capital and Training in Achieving SDG-aligned Success of Entrepreneurs - Abdullah, Aseela; Riaz, Kashif; Jan, Amna; Wahab, Anosha (Pakistan Journal of Humanities and Social Sciences, 2023)
The issue addressed in this study holds importance as it explores the significant role of microfinance institutions in fostering entrepreneurial success through the provision of non-financial services. Employing a quantitative research design, the study examines the impact of these factors on the success of entrepreneurs within the microfinance sector in Pakistan. The collected data analyze through statistical softwares, such as SPSS and PLS-SEM. The findings reveal a positive and significant impact of social capital on the success of entrepreneurs, indicating that entrepreneurs with strong social networks, access to resources, and positive reputation are more likely to succeed. Similarly, training and development are found to have a positive and significant influence on entrepreneurial success, highlighting the importance of continuous learning and skill development for entrepreneurs. The study also identifies a moderating effect of entrepreneurial experience, suggesting that the positive impact of training and development is stronger for individuals with higher levels of experience. These findings emphasize the importance of financial inclusion and its potential to drive economic growth and reduce inequalities in Pakistan. Despite limitations in sample size and context, this study provides valuable insights for future research and the development of effective strategies to support entrepreneurial growth and development in the microfinance sector.